Likelihood of using online banking services among consumers: application of logit model - Duasa, Jarita; Zainan Nazri, Nurul Jannah; Zainal, Nur Hidayah (Malaysian Consumer and Family Economics Association (MACFEA), 2019)
Research on the area of internet banking has been extensively studied in developing countries since internet banking resumed from the new millennium. Most studies on this topic were conducted in Asian countries. Most methods adopted are attempted to analyze the ‘perception' among respondents or consumers on this technology. Very limited studies were using logit or probit regression to explore the ‘probability’ or ‘likelihood’ of consumers using internet banking, in particular among Malaysian consumers. The current study aims to analyze the probability of using digital banking services among consumers in Malaysia using survey data collected in the area of Klang Valley. Responses from the survey are analyzed empirically using logistic regression and the study finds that regardless of the choice of consumers on banks whether it is local or foreign, Islamic or conventional and regardless of how often they visit the bank(s), the likelihood of using online banking is significantly determined by the level of education they have, gender and category of employment. There is a higher probability of choosing online banking services among those who are highly educated, females and those who are not working in the government sector.